Input significance analysis: feature ranking through synaptic weights manipulation for ANNS-based classifiers - Hassan, Raini; Taha Alshaikhli, Imad Fakhri; Ahmad, Salmiah (University of El Oued, 2017)
Due to the ANNs architecture, the ISA methods that can manipulate synaptic weights selected are Connection Weights (CW) and Garson’s Algorithm (GA). The ANNs-based classifiers that can provide such manipulation are Multi Layer Perceptron (MLP) and Evolving Fuzzy Neural Networks (EFuNNs). The goals for this work are firstly to identify which of the two classifiers works best with the filtered/ranked data, secondly is to test the FR method by using a selected dataset taken from the UCI Machine Learning Repository and in an online environment and lastly to attest the FR results by using another selected dataset taken from the same source and in the same environment. There are three groups of experiments conducted to accomplish these goals. The results are promising when FR is applied, some efficiency and accuracy are noticeable compared to the original data.